The effect of some environmental factors that affecting daily milk yield of Iraqi buffaloes in Ninewah: Garabed A. Avadesian1, Alaa S. Al – Haddad2, Odday S. Al – Obaddy2, Nassar N.Al – Anbari1 and Ali S. Sadiq2 - Avadesian, Garabed A. (The Iraqi Journal of Veterinary Medicine, 2012)
This study was carried out on the local buffalo in Ninewah, data were collected from154 buffalo in two herds during the period 1/7/2010 until 18/7/2010 in which milk collected daily in sequence ( 1st day , 5th day , 9th day , 13th day and 17th day ) and recording maximum and minimum temperature .Data were analyzed using general linear model ( GLM) within SAS program to study the fixed effects ( parity , herd , stage of lactation and test day ) , and regression coefficient with heritability . Overall average daily milk yield was 9.69 ± 0.12 kg and it appeared that parity , herd and stage of lactation has a highly significant effects in daily milk yield , while test day recorded no significant effect in the above . Minimum temperatures ranged (23.5 – 27.5 °C) and maximum was (41.8 – 45.6 °C). Regression coefficient for daily milk yield on maximum temperature was -0.259 kg / °C on (P > 0.01) and for minimum was 0.0325 kg / °C and this was non - significant, while the prediction equation (ŷ) was:Y^ (max) = 21.121 – 0.259 (X1)Y^ (min) = 8.863 + 0.0325 (X2)The heritability estimate for daily milk yield was ranged between (0.17 – 0.21) for the test day (recording day) , it was concluded that from this a number of fixed effects , and yield was decreased significantly with rising in ambient temperature and the estimates of heritability for daily milk yield belonged to test day was rather low.